2014
DOI: 10.1111/bdi.12202
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol for mania: a randomized trial of allopurinol versus placebo as add‐on treatment to mood stabilizers and/or antipsychotic agents in manic patients with bipolar disorder

Abstract: The findings of this large, well-powered study do not support add-on allopurinol as a treatment for acute mania. This study did not test the efficacy of allopurinol as monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…Antimanic efficacy has not been demonstrated for allopurinol (level 1 negative),167 eslicarbazepine/licarbazepine (level 2 negative),168 gabapentin (Level 2 negative), lamotrigine (level 1 negative),143 omega‐3 fatty acids (level 1 negative),169 topiramate (level 1 negative),143 valnoctamide (level 2 negative),170, 171 or zonisamide (level 2 negative)172 (Table 13). …”
Section: Acute Management Of Bipolar Maniamentioning
confidence: 99%
“…Antimanic efficacy has not been demonstrated for allopurinol (level 1 negative),167 eslicarbazepine/licarbazepine (level 2 negative),168 gabapentin (Level 2 negative), lamotrigine (level 1 negative),143 omega‐3 fatty acids (level 1 negative),169 topiramate (level 1 negative),143 valnoctamide (level 2 negative),170, 171 or zonisamide (level 2 negative)172 (Table 13). …”
Section: Acute Management Of Bipolar Maniamentioning
confidence: 99%
“…Another recent study found no difference between allopurinol (at a lower dose, 300mg/day) and placebo in BD patients experiencing an acute manic episode. However, these patients were treated with a variety of mood stabilizers and antipsychotics, potentially causing a ceiling effect (Weiser et al, 2014). Unfortunately, the authors provided no information on the number of concomitant medications, dose, or even the duration of treatment with mood stabilizers and antipsychotic medications during the follow-up period (Weiser et al, 2014), which prevents consistent conclusions from being drawn.…”
Section: Treatment-related Studies and Clinical Trialsmentioning
confidence: 99%
“…However, these patients were treated with a variety of mood stabilizers and antipsychotics, potentially causing a ceiling effect (Weiser et al, 2014). Unfortunately, the authors provided no information on the number of concomitant medications, dose, or even the duration of treatment with mood stabilizers and antipsychotic medications during the follow-up period (Weiser et al, 2014), which prevents consistent conclusions from being drawn. More recently, a four-week, double-blind, placebo-controlled trial with allopurinol (300mg/day) as an add-on treatment to valproate showed significant antimanic effects compared to placebo (Jahangard et al, 2014).…”
Section: Treatment-related Studies and Clinical Trialsmentioning
confidence: 99%
“…It has been hypothesized that a reduced adenosinergic activity, mostly at A1 receptors (with an increase in uric acid levels), is associated with the complex found that the purinergic modulator allopurinol, a xanthine oxidase inhibitor used for the treatment of gout and hyperuricemia, is effective in treating acute mania when used adjunctively with lithium (Machado-Vieira et al, 2008), lithium and haloperidol (Akhondzadeh et al, 2006), and sodium valproate (Jahangard et al, 2014). A recent large, well-powered, placebo-controlled study, however, did not find allopurinol addition to mood stabilizers (other than lithium) and/or antipsychotic (taken for a period of between three days and two weeks) more effective than placebo in manic patients (Weiser et al, 2014). A possible explanation of this discrepancy is that allopurinol might have a different effect in combination with different mood stabilizers.…”
Section: Introductionmentioning
confidence: 99%
“…However, controversies also exist: two negative studies failed to show a benefit of adding allopurinol in mania (Fan et al, 2012;Weiser et al, 2014); Salvadore et al, 2010 failed to confirm a correlation between serum uric acid levels and YMRS scores in manic subjects.…”
Section: Introductionmentioning
confidence: 99%